Finite Element Modelling of RC T - Beams Reinforced Internally with GFRP Reinforcements - R., Balamuralikrishnan; J., Saravanan (Civil Engineering Journal, 2019)
Fibre reinforced polymers (FRP) are being used extensively in the rehabilitation and retrofitting of existing structuresÂ  as an external reinforcement because of their properties like high strength to weight and stiffness to weightÂ  ratios, corrosion resistance, light weight and high durability. They are especially used in the reinforced concrete structure like bridges, chimney, high rise building etc. At present FRP reinforcements are available in the form of reinforcing bars and are used in the structures in place of steel, mainly the structures are constructed near the coastal areas or in the aggressive environments. The main advantage of FRP rebar is its corrosion resistance, light weight, durability and easy handing. The FRP rebars are being used worldwide for many structures including bridge structures as well, but not well explored because of its availability. The main objective of this thesis work is to assess the static load behaviour of RC T-beams reinforced internally with GFRP reinforcements using finite element analysis software ANSYS. Totally twelve numbers of specimens were considered in this study with varying parameters such as type of reinforcements, reinforcements ratio and concrete grade. Modelling of the T- beams were done with ANSYS using solid 65 and link 8 element and the same were analyzed under static loading conditions. The results obtained from the ANSYS were compared with the theoretical and experimental analysis. Based on the comparison suitable conclusions and recommendations are made in this research work.